2013
DOI: 10.1155/2013/256280
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Fibromyxoid Sarcoma: Incidence, Treatment Strategy of Metastases, and Clinical Significance of theFUSGene

Abstract: Aim. The aim of this study was to assess the incidence of low-grade fibromyxoid sarcoma (LGFMS), present treatment results of metastatic LGFMS, and investigate the clinical significance of the FUS gene rearrangement. Methods. This study included 14 consecutive LGFMS patients treated at the Aarhus Sarcoma Centre in 1979–2010. Fluorescent in situ hybridization (FISH) analysis for FUS break-apart was performed for all patients. Results. The incidence of LGFMS was 0.18 per million, representing 0.6% of all soft ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 21 publications
0
82
0
Order By: Relevance
“…Both the CREB3L2 and CREB3L1 genes encode transcription factors [6] . A single-centre retrospective review of 14 patients with LGFMS found no association between the presence of the FUS-CREB3L2 fusion gene and local recurrence or metastatic disease [4] .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Both the CREB3L2 and CREB3L1 genes encode transcription factors [6] . A single-centre retrospective review of 14 patients with LGFMS found no association between the presence of the FUS-CREB3L2 fusion gene and local recurrence or metastatic disease [4] .…”
Section: Discussionmentioning
confidence: 98%
“…In the aspect of molecular biology, chromosomal translocations are found in nearly all patients with LGFMS. The t(7;16)(q32-34; p11) chromosomal translocation and the resulting fusion of FUS RNA binding protein (FUS)-cAMP responsive element binding protein 3-like 2 (CREB3L2) is the most frequently seen (75-95% of patients with LGFMS), whilst the FUS-CREB3L1 fusion gene is present in approximately 5% of cases of LGFMS [4,5] . Both the CREB3L2 and CREB3L1 genes encode transcription factors [6] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Involvement of acral sites is not highly emphasized in the literature. After encountering this case, we reviewed the literature and found 24 cases (mostly embedded in case series) of LGFMS involving distal extremities and acral sites (Table ) …”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is reserved for patients whose tumors recur locally or spread to distant sites [14] [15]. No adjuvant treatments were administered to our patient as they would have been unconventional for low-grade fibromyxoid sarcoma.…”
Section: Discussionmentioning
confidence: 99%